Enhancing Entrepreneurship Resource Competence through Business Incubator Consultant Certification - Halim, Hendra; Ramadhani, Evi; Kadriadi, Kadriadi; Aziz, Fauzan; Subakty, Edhy; Susiatmojo, Amin; Putra, I Gede Juliana Eka (Asian Journal of Community Services, 2024)
This paper presents the results of a certification program aimed at enhancing the competency of entrepreneurship resources through the certification of business incubator consultants. The program, conducted by the Indonesia Management Forum and HR24/7 Communication Hub in Bali, involved participants from various regions across Indonesia. The training sessions covered topics such as advocacy for technology business incubator development, product-market fit analysis, business idea validation, feasibility study preparation, legal and institutional management, company profile creation, access to financing, marketing assistance, business valuation, and financial report preparation. The program culminated in a competency assessment on the third day. The results indicated a high level of satisfaction among participants, highlighting the program's effectiveness in improving their understanding and skills in technology business incubator management. The implications of this program include the potential enhancement of Indonesia's entrepreneurship ecosystem and contributions to the achievement of Sustainable Development Goals.